Depiction of trust in mother - Situmorang, Nina Zulida; Muhopilah, Pipih; Nasywa, Naila; Missasi, Vallahatullah (Universitas Muhammadiyah Surakarta, 2020)
Abstract. Mother is person who very close to her child, mother always caring and pay attention, this closeness creates child's trust to his mother. Trust is what makes children feeling that the mother is the most comfortable people to share all their complaints without demeaning. This study aims to explore the child's closeness with his mother and the reason. This research used qualitative research with constructive realism method, the subject of this research are 60 students that aged 20-28 years, the subject was asked: